Cloning and Characterization of Oleoyl-Coa Desaturase Gene from Oil Palm (Elaeis Guineensis L.) - Shahwan, Syahanim (2006)
Oil palm (Elaeis guineensis) is the main commodity crop in Malaysia. Oil palm is the second largest producer of vegetable oil in world vegetable oil markets with revenue of RM28.6 billion. Storage oil derived from oil palm contains 50% saturated, 40% unsaturated fatty acids and 10% polyunsaturated fatty acids. The oleoyl Co-A desaturase (FAD2; E.C 1.3.1.35) is involved in the production of polyunsaturated fatty acids. The enzyme utilizes oleic acid (C18:1) to produce linoleic acid (C18:2) by adding the second double bond at the 12th carbon of oleic acid. As high levels of oleic acid are often desirable for industrial applications, genetic manipulation via antisense technology and seed-specific suppression can be attempted to silence this gene, to manipulate the level of oleic acid to suit various downstream applications. In this study, two specific primers (PD1As and PD2) were designed based on the conserved region of FAD2 sequences from other plant species. A partial gene of 350 bp in length was amplified and the partial region has a high percentage of sequence identities (91%) with other FAD2 genes from various plant species such as Brassica campestris, Brassica rapa and Crepis palaestina. The complete sequence, designated EgFAD2, which is 1510 bp in length, consisting of 391 amino acids in its open reading frame was obtained via rapid-amplification of cDNA ends – polymerase chain reaction (RACE-PCR). The polypeptide carried three histidine clusters that were conserved among the desaturase genes. The deduced amino acid sequences showed significant identity to other plant FAD2 proteins such as Oryza sativa (75%), Glycine max (72%) and Punica granatum (71%). In addition it has the aromatic residues (-YNNTL) at the C-terminus similar to other gene targeted to be expressed in endoplasmic reticulum. Northern blot was carried out to analyze the expression profile of this gene in various tissues of oil palm. The oil palm oleoyl-CoA desaturase gene was highly expressed at the later stages of mesocarp tissue development (15-, 17- and 20- week after anthesis) with the strongest signal at week-15. The expression of the transcript correlated with the levels of linoleic acid deposited in the mesocarp as the fatty acids begin to accumulate in mesocarp tissues at week-15. The results also showed that the gene plays an important role for oil storage as the oil deposition starts at week-15 in the oil-bearing tissue. Southern analysis indicated the existence of at least two to four copies of oleoyl-CoA desaturase gene in the oil palm genome. The open reading frame of the oil palm oleoyl-CoA desaturase was expressed as a fusion protein in E. coli. The expected size of 44 kDa was obtained. However, the expression construct had to be further confirmed. In a conclusion, the findings of this study could aid the development of high oleic trait in oil palm by manipulating the full-length gene of oleoyl-CoA desaturase and will serve as an initial step for future biochemical characterization of the encoded product of this gene.